The Last Gasp of Neoliberalism - Watkins, John P.; Seidelman, James E. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
The ideas of both Thorstein Veblen and Karl Polanyi shed light on understanding the last gasp of neoliberalism. The last gasp refers to Donald Trump's abandonment of free trade, long considered a cornerstone of the neoliberal agenda, and his overt attacks on democratic institutions. In Trump, neoliberalism's attempt to overcome the gridlock of liberal democracy has revealed its fascist leanings. Both Polanyi and Veblen warned about the trend towards fascism. Trump was elected, in part, by filling the void left by the factioning of neoliberalism, in part by the injustice felt by people in rural areas, those with stagnant incomes, white males, and others. Trump has transcended the neoliberal agenda, approaching market relations from the point-of-view of the fight. The emergence of a predatory culture, in both the domestic and international realms, resembles the culture outlined in Veblen's The Theory of Business Enterprise. Trump's actions reveal the need to extend Polanyi's idea of social protection given the negative effects of modern technology and Trump's efforts to dismantle or reduce some regulatory agencies. Changing demographics and the adverse reaction to Trump's fascist leanings may yet see the emergence of a new progressive era, suggesting, at least, that Trump represents the last gasp of neoliberalism.
Keywords: POLANYI, Karl, 1886-1964; VEBLEN, Thorstein, 1857-1929; capitalism; democracy; double movement; fascism; international relations; neoliberalism